RELEVANCE OF ANESTHESIA FOR MINOR SURGERY - I. B. Xayitov; N. M. Malikov (Journals Park Publishing, 2023)
Adequate pain management is one of the main tasks of outpatient surgery and includes intraoperative anesthesia, postoperative pain reduction and chronic pain management. General anesthesia is not possible in outpatient surgery settings. Analgesia is necessary in postoperative period and in patients with non-surgical pathology. Analgesic effect of various drugs is related to direct analgesia, decreasing of inflammation and tissue edema or indirect influence on pain syndrome. Narcotic analgesics include opium derivatives and drugs (morphine, promedol), Their mechanism of action is mediated through opioid receptors on the cellular or systemic level. Non-narcotic analgesics include nonsteroidal anti-inflammatory drugs (NSAIDs). Ketorolac, nonselective inhibitor of cyclooxygenase and prostaglandins synthesis, has the strongest analgesic effect. Ketorolac efficacy is comparable to narcotic analgesics, but it does not cause respiratory depression and drug dependence, has no sedative and anxiolytic effects.
Keywords: ambulatory surgery, anesthesia, analgesics, ketorolac.